The Effect of Focus Film Distance Variation on Patient Absorbed Dose in Thorax Examination with Roentgen Machine in Radiology Installation of Sanjiwani Hospital Gianyar - I Nyoman Yosua; Gusti Ngurah Sutapa; I Ketut Putra; Ida Bagus Suryatika; Hery Suyanto; Ida Bagus Alit Paramarta (Universitas Hamzanwadi, 2024)
A study has been conducted on the effect of Focus Film Distance (FFD) variation on patient absorbed dose during thorax examination at the Radiology Installation of Sanjiwani Hospital, Gianyar. This study aims to determine the effect of FFD variation and the suitability of the radiation dose received by patients whether it is still within the limits of BAPETEN's decision. The X-ray machine used was Siemens Luminos Fusion Roentgen with the FFD variation method given a distance of 110 cm, 130 cm, and 150 cm in 30 patients. Dose measurements were carried out based on radiation exposure and analyzed according to BAPETEN standards. The results showed that the greater the FFD value, the smaller the absorbed dose received by patients. The highest absorbed dose obtained for FFD 110 cm was 0.3867 mGy, 130 cm was 0.2769 mGy, and 150 cm was 0.2079 mGy below the maximum limit of 0.4 mGy set by BAPETEN, so it is safe for patients. Statistical analysis of one-way t-test showed significant results, with thitung < ttabel. This indicates that FFD variation affects the absorbed dose, and all doses remain within safe limits. Thus, thorax examination at RSUD Sanjiwani Gianyar has met the established safety standards.